Effects of dietary pyrroloquinoline quinone on growth performance, serum biochemical parameters, antioxidant status, and growth-related genes expressions in juvenile yellow catfish, Pelteobagrus fulvidraco - Shi, Qingchao; Wen, Zhengyong; Wang, Jun; Hu, Peng; Zou, Yuanchao; Wang, Shuqi; Qin, Chuanjie (Frontiers in Marine Science, 2022)
This study aimed to evaluate the impacts of dietary pyrroloquinoline quinone (PQQ) supplement on growth performance, serum biochemical parameters, antioxidant status, and growth-related genes expressions in juvenile yellow catfish, Pelteobagrus fulvidraco. Triplicate groups of fish (n = 40) with an average weight of 5 g were fed with five gradient levels PQQ-incorporated diets (0 (basal), 1.5 mg/kg; 3.0 mg/kg; 4.5 mg/kg, 6.0 mg/kg) for 56 days. Our findings revealed that fish fed with the diets containing PQQ at the level of 3.0-6.0 mg/kg showed significantly higher final body weight, weight gain rate, and specific growth rate than those of that in the control group (P < 0.05). The activities of protease were observed significantly increased in fish fed with diets containing 4.5 mg/kg and 6 mg/kg PQQ (P < 0.05). Meanwhile, fish in 4.5 mg/kg PQQ group showed significantly lower levels of serum total cholesterol, triglycerides, and low-density lipoprotein cholesterol, and significantly higher level of the high-density lipoprotein cholesterol (P < 0.05). The antioxidant-related parameters of superoxide dismutase and total antioxidant capacity were markedly elevated (P < 0.05), while malondialdehyde content was significantly reduced in 3.0-6.0 mg/kg PQQ group (P < 0.05). Meanwhile, the mRNA expression levels of growth-related genes (growth hormone, insulin-like growth factor 1, and insulin-like growth factor 2) were dramatically up-regulated in the liver of fish fed with the diets containing 3-6 mg/kg PQQ in comparison with the control group (P < 0.05). In conclusion, dietary PQQ could improve the growth performance, serum biochemical parameters, antioxidant status, and growth-related genes expressions in juvenile yellow catfish, and the optimal dietary PQQ level was evaluated to be 4.92 mg/kg of dry diet for juvenile yellow catfish.